2003
DOI: 10.1211/0022357021972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient opinions in a pharmacy-level intervention study

Abstract: ObjectiveTo explore patients' satisfaction with their community pharmacy's services and to evaluate the effects of an intervention programme in which a trained technician organised patient education activities in the pharmacy. MethodWe surveyed patients visiting the participating pharmacies at three stages: at the start of the intervention period (0 months, T0), at the end (after 12 months, T1), and 12 months after the intervention had been completed (24 months from baseline, T2). At each stage, 500 questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…In one study, however, high levels of patient satisfaction were reported despite sub-optimal ratings for counselling levels [39]. Another interesting observation was the high levels of baseline satisfaction reported prior to any intervention delivery [43]. High satisfaction ratings with different cognitive services were also observed in all reviewed studies.…”
Section: Summary Of Patient Satisfaction Evaluationsmentioning
confidence: 88%
See 3 more Smart Citations
“…In one study, however, high levels of patient satisfaction were reported despite sub-optimal ratings for counselling levels [39]. Another interesting observation was the high levels of baseline satisfaction reported prior to any intervention delivery [43]. High satisfaction ratings with different cognitive services were also observed in all reviewed studies.…”
Section: Summary Of Patient Satisfaction Evaluationsmentioning
confidence: 88%
“…Administration modes ranged from self completion on site [42,44,47,51], provider/researcher administered either on site (face to face interviews) [28,32], or via telephone [40,41,46], or mailed [30,34,39,43,45,[47][48][49][50]. One innovative study reported the use of trained volunteer patients as 'mystery shoppers' to assess and report their satisfaction with services provided by different health care professionals [36].…”
Section: Methods Of Satisfaction Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with results of observational studies in the past, these Dutch community pharmacies increased their level of communication about drug side-effects [17,25]. Apparently, the use of a computer checklist helps to guarantee the presentation of required information items.…”
Section: Discussionmentioning
confidence: 98%